2023
DOI: 10.1108/apjml-02-2023-0108
|View full text |Cite
|
Sign up to set email alerts
|

The roles of social media and mutual relationships between travel attitudes and brand equity

Yung-Chuan Huang

Abstract: PurposeThe purpose of this study has to conduct an integrated effective evaluation system to discover consumers' travel attitudes of the culinary experiences or cuisines and establishing an optimal mutual relationship of a brand equity evaluation model.Design/methodology/approachBased on a sample of 624 participants, the results support that social media engagement has indirect effects on culinary brand equity development through travel attitudes and information sharing.FindingsThe study finds that values are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…This suggests that consumers might assume that MC helps to acquire social status, image, and self-concept; to put it another way, social image congruence can be improved by utilizing MC. According to Huang (2023), value expression has a positive relationship with how we experience travel and the extent to which we are attached to food brands in culinary tourism. This value is an important part of self-identity that influences an individual's attitude and loyalty when traveling.…”
Section: Perceived Value On Tourist Attitudesmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that consumers might assume that MC helps to acquire social status, image, and self-concept; to put it another way, social image congruence can be improved by utilizing MC. According to Huang (2023), value expression has a positive relationship with how we experience travel and the extent to which we are attached to food brands in culinary tourism. This value is an important part of self-identity that influences an individual's attitude and loyalty when traveling.…”
Section: Perceived Value On Tourist Attitudesmentioning
confidence: 99%
“…Social media has a significant role in mediating the relationship between advertising and online shopping (Nasidi et al, 2022). A study by Huang (2023) found that social media plays a significant mediating role in the relationship between social media engagement and brand equity. Social media in this digital era has become a communication channel that influences attitudes, behavioral intentions, and actual human behavior.…”
Section: The Mediating Effect Of Social Media Use Between Tourist Kno...mentioning
confidence: 99%